2006
DOI: 10.4049/jimmunol.176.5.3000
|View full text |Cite
|
Sign up to set email alerts
|

Expression of B7-H1 on Gastric Epithelial Cells: Its Potential Role in Regulating T Cells during Helicobacter pylori Infection

Abstract: Helicobacter pylori infection is associated with gastritis, ulcers, and gastric cancer. The infection becomes chronic as the host response is unable to clear it. Gastric epithelial cells (GEC) play an important role during the host response, and their expression of class II MHC and costimulatory molecules such as CD80 and CD86 suggests their role in local Ag presentation. Although T cells are recruited to the infected gastric mucosa, they have been reported to be hyporesponsive. In this study, we detected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
145
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 54 publications
(51 reference statements)
8
145
0
1
Order By: Relevance
“…Similarly, in infected mice, depleting the Treg cells led to increased pathology (20,21). Since Treg cells may play an important role in the impaired T-cell responses during H. pylori infection, and we and others have shown that B7-H1 also plays a role in T-cell suppression or generation of Treg cells (5,12,30), we sought to determine the role of B7-H1 on GEC in the development of CD4 ϩ CD25 high FoxP3 ϩ Treg cells during H. pylori infection. In this study, we show that coculture of naïve CD4 ϩ T cells with H. pylori-exposed GEC generates CD4 ϩ CD25 high FoxP3 ϩ T cells.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Similarly, in infected mice, depleting the Treg cells led to increased pathology (20,21). Since Treg cells may play an important role in the impaired T-cell responses during H. pylori infection, and we and others have shown that B7-H1 also plays a role in T-cell suppression or generation of Treg cells (5,12,30), we sought to determine the role of B7-H1 on GEC in the development of CD4 ϩ CD25 high FoxP3 ϩ Treg cells during H. pylori infection. In this study, we show that coculture of naïve CD4 ϩ T cells with H. pylori-exposed GEC generates CD4 ϩ CD25 high FoxP3 ϩ T cells.…”
mentioning
confidence: 63%
“…Since binding of B7-H1 to the programmed death 1 receptor on T cells causes them to undergo anergy or apoptosis (23,27), B7-H1 may play a key role in the chronicity of those infections and associated inflammatory responses. H. pylori-exposed GEC incubated with isolated CD4 ϩ T cells resulted in decreased proliferation and IL-2 production, but this inhibition was abrogated by anti-B7-H1 blocking antibodies (5). These findings suggest that B7-H1 plays an important role in T-cell inhibition during H. pylori infection.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Hence, it was shown that the PD-1:PD-Ls pathway contributes directly to T cell dysfunction and lack of viral control in established chronic infection both in mice (35) and humans (36 -38). Similarly, persisting infection with pathogens other than viruses, like Helicobacter pylori and Porphyromonas gingivalis, showed elevated expression of PD-L1 on gastric epithelial cells (39) and monocytes (40), respectively, suggesting a potential involvement of PD-L1 in promoting chronic infection (39). However, the function of the PD-1:PD-Ls interactions during the regulatory pathways that contribute to persistence of intracellular bacteria has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, during hepatitis B virus infection, PD-1:PD-L1 interactions were shown to contribute to the suppression of IFN-␥ secretion following Ag recognition in the liver (59). Furthermore, in infection with H. pylori, anti-PD-L1 was shown to increased T cell proliferation and IL-12 secretion (39). Accordingly, in this work we demonstrated that the PD-1:PD-Ls pathway displayed a coinhibitory role on IFN-␥ production during chronic M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%